Kecelakaan Kerja Di PT. Cipta Kridatama Batulicin - Adi Nugroho; Suci Widyawati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Background: An accident in work is unexpected incident for everyone and also the worker. There are so many factors as cause among human behavior, environment and tools. The purpose of this research knows the correlation between safety work using behavior and an accident incident at PT. Cipta Kridatama Batulicin period 2007 – March 2008. Method: This research used analytic observational research with case control approach. The research sample is workers at PT. Cipta Kridatama Batulicin Kabupaten Tanah Bumbu which consist of 40 cases and 40 control.Result: The result of this research show that workers who experience an accident are they are who age between 27 – 31 years old (27,5%), senior high school grade (42,5%), operation department (82,5%) and long work for until 4 – 6 years (57,5%). Chi square examination with ± = 0,05 shows that worker knowledge (p = 0,014), worker attitude (p = 0,019), using safety work practice (p = 0,003 and OR = 4,394) and safety work using behavior (p = 0,022). The conclusion of this research is there is correlation among worker knowledge, worker attitude, safety work using practice and safety work using behavior with an accident in work.